Legal Protection for Consumers of Non-Compliant Iodized Edible Salt Not Meeting SNI Standards in Tegal Regency - Annisa Cahya Madani; Baidhowi Baidhowi (Faculty of Law, Universitas Negeri Semarang, 2025)
Iodine deficiency or Iodine Deficiency Disorders (IDD) remain a nutritional challenge in Indonesia. Iodized table salt should be the solution, but in Tegal Regency, many salt products were found to not meet SNI 3556:2016 standards. This study aims to analyze the legal protection mechanisms for consumers of iodized table salt that does not meet SNI standards in Tegal Regency. The method used is empirical legal research with a qualitative approach. Data was collected through interviews with the Tegal Regency Health Office and LP2K Central Java, as well as literature review. The results of the study indicate that legal protection is still not functioning optimally, as the GAKY Task Force in Tegal Regency is no longer active and there is no specific local regulation on GAKY mitigation. On the other hand, LP2K Central Java remains actively involved through sample testing and policy advocacy. This study emphasizes the importance of institutional strengthening and enforcement of the law in ensuring consumers' rights to safe and standard-compliant food products.